An Examination of Environmental Disclosures in UK Corporate Annual Reports - Aly Salama; Robert Dixon; Murya Habbash (Journal of Accounting, Business and Management (JABM), 2012)
Although there have been a substantial number of prior studies which have investigated the relationships between corporate characteristics and environmental disclosure, few have been applied to UK data and none have explored model specification issues. We find that size and industry have significant positive impact upon environmental disclosures while profitability has a negative impact upon disclosures. We suggest that future research should pay greater attention to model specification. Accordingly, whilst we can claim that corporate characteristics are highly indicative of a tendency for managers to offer greater disclosure, researchers need to make their claims with more care. Further investigations of the impact of profitability on discretionary environmental disclosures are likely to offer additional insight. In particular, the apparent relationship between specific and voluntary areas of disclosure and negative financial performance has some important implications for future empirical work and the development of accounting theory.